Effectiveness of Jigsaw Type Learning Model on Mathematics Learning Outcomes - Anissatussa’diyah, Anissatussa’diyah; Widiyono, Aan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to evaluate the effectiveness of implementing the Jigsaw learning model in improving mathematics learning outcomes among fourth-grade students at SD Negeri 2 Kuanyar. The study involved 21 students as subjects, employing a quantitative approach with a one-group pre-test and post-test design. Data collection was conducted using learning outcome tests in each learning cycle. The results indicate that the use of the Jigsaw model significantly positively impacts students' learning outcomes. Data analysis using this method shows a mean value of -29.523, with a standard deviation of 9.47428 and a standard error mean of 2.06746. Furthermore, the obtained t-value is -14.280, with a two-tailed significance of 0.000. Since the significance value is smaller than 0.05 (0.000 < 0.05), this indicates a significant effect of the learning model on students' learning outcomes. The Jigsaw learning model plays a crucial role in enhancing students' attention and interest during the learning process. This model encourages students to be more confident, responsible, and actively engaged in problem-solving within their groups, making it effective in improving the mathematics learning outcomes of fourth-grade students at SD Negeri 2 Kuanyar.